Strengthening Provincial Role in Disaster Preparedness: A Case Study of The Local Agency for Disaster Management at Lampung - Arinaldi, Julian (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
This study explores the preparedness level in Lampung province and answer how it can be strengthened to conduct an effective response to facing disaster, especially by the Local Agency for Disaster Management (Badan Penanggulangan Bencana Daerah or BPBD) of Lampung as the main stakeholder of disaster management in the Province of Lampung. This study used descriptive qualitative research method. The findings show that the recent mechanism of disaster management provides an adequate mandates to support implementation at the sub-national level; however it also provides a sign that domestic disaster-related tasks, such as preparedness, have potent dependence on the national level especially due to the lack of ability of the local government to provide resources. The findings suggest that coordination (or collaboration/networking) among various levels of government (hierarchical networking) and between governments at the same level (horizontal networking) are needed to expand resources for effective preparedness to disaster management.